Phenotypic evaluation of scutellum-derived calluses in ‘Indica’ rice cultivars - Arman PAZUKI; Mohammad Mehdi SOHANI (Acta Agriculturae Slovenica, 2013)
By using amenable MS based medium containing 4 mg l-1 2,4-Dichlorophenoxyacetic acid (2,4-D), 0.4 mg l-1 benzyl-aminopurine (BAP), 30 g l-1 sucrose, 8 g l-1 Agar-agar, qualitative and quantitative traits of calluses initiated from four genetically and commercially valuable Northern Iranian rice cultivars including Hashemi, Hasani, Gerdeh, and Gharib were studied. Five seeds were placed in each Petri dish and three replicates of eight Petri dishes per replicate were incubated in a growth chamber at 25 ±2 °C in the dark and the averages for every replicate were employed in the analyses. Several important parameters related to callogenesis of the cultivars including rate of non-viable seeds, necrotic, scutellar, slow growing, and non-scutellar calluses, simultaneous callus induction from scutellar and non-scutellar tissues, seeds with appropriate callus, and root emergence were compared. Accordingly, calli of Gharib and Hashemi were highly responsive in callogenesis, while Gerdeh and Hasani produced dissatisfying calluses. Necrotic calluses, scutellar calli, and non-viable seeds were positively correlated with each other; although they were negatively correlated with non-scutellar calli, simultaneous scutellar and non-scutellar calli induction, and root emergence. The results of the present study are expected to be the first promising step to generate genetically manipulated Iranian indigenous rice cultivars.